The Balance 0f Knowledge And Spirituality Of Ghazali’s Persepective - Siti Nudia Amburika; Nasikhin; Mustopa (ARIMA : Jurnal Sosial Dan Humaniora, 2025)
The balance between science and spirituality is a fundamental concept in Al-Ghazali's thought that offers a solution to the modern dichotomy between mind and heart. This article aims to analyze Al-Ghazali's perspective on the integration of science ('ilm) and spirituality (tazkiyatun nafs) as two complementary aspects in achieving happiness in this world and the hereafter. Using the library research method, this article examines how Al-Ghazali emphasizes the importance of knowledge that is not only cognitive, but also accompanied by purification of the soul to avoid intellectual arrogance. Conversely, spirituality without the basis of true knowledge can lead a person to misguidance. The findings of this article show that Al-Ghazali's concept is relevant in the present context, where humans face a crisis of meaning due to the dominance of secular science that ignores the transcendental dimension. Thus, Al-Ghazali's synthesis of science and spirituality can be a holistic framework for the development of ethical and divinity-oriented science.